ENGARUH KUALITAS PRODUK DAN PELAYANAN TERHADAP KEPUASAN PELANGGAN DI MIYAZAKI JAPANESE GRILL HANGOUT KOTA SORONG - Zain, Evi Mufrihah; Zahra, Ayu Anisah (STIE Perbankan Indonesia, 2024)
Customer satisfaction is the level of someone's feelings after comparing the perceived performance (results) with their expectations. Good product quality and service can influence customer satisfaction. This research aims to find out how much influence product and service quality has on customer satisfaction at Miyazaki Japanese Grill Hangout, Sorong City. The type of research used was quantitative research with a descriptive approach using incidental sampling during March 2024 for Miyazaki Japanese Grill Hangout customers who purchased more than once, resulting in a sample of 87 respondents. The results obtained from this research are that product quality variables have a partial positive and significant effect on customer satisfaction, partial service has a positive and significant effect on customer satisfaction, and product and service quality simultaneously has a positive and significant effect on customer satisfaction.